Unicorns transforming the practice of urology: value creation and allocation in the digital age - Erben, Philipp; Rodler, Severin; Turki, Amin T.; Witzsch, Ulrich; Thielscher, Christian (World journal of urology, 2025)
Purpose To analyze what kind of products and services unicorns, which create a substantial financial value, provide in urology and what this means for the future of urological practice. So far, the added value of unicorns has hardly been utilised for medical research, although a fraction of it would be enough to multiply the funds for urological research. Methods All medical unicorns (as by end of 2024) were studied, and urological unicorns identified. Publicly available data on valuation, investors, business operations and geographic distribution were analyzed to determine entrepreneurial purpose and value creation in urology. Results Among the 21 unicorns in urology, the majority operate in drug research, including artificial intelligence guided development; this is in line with the digital transformation of medicine. Yet, business models are diversified. The valuations range from $ bn 1.0 to 7.83, summing to a total value of $ bn 56.2. The overwhelming majority (90%) is based in the US, one in China and one in UK. Conclusion Unicorns in urology have accumulated substantial financial impact, which may accelerate medical progress but also creates risks (such as creating inequity). These developments will likely impact the practice of urology and deserve more scientific research to inform medical societies and policy decision making.
Online veröffentlicht: 16. Juli 2025
Gesehen am 02.09.2025